Indications of magnetic coupling effects in spin cross-over molecular thin films. Issue 8 (10th January 2018) - Zhang, Xin; N'Diaye, Alpha T.; Jiang, Xuanyuan; Zhang, Xiaozhe; Yin, Yuewei; Chen, Xuegang; Hong, Xia; Xu, Xiaoshan; Dowben, Peter A.
Abstract : Room temperature isothermal reversible spin crossover switching of [Fe(H2 B(pz)2 )2 (bipy)] thin films by external magnetic fields is demonstrated. Abstract : Room temperature isothermal reversible spin crossover switching of [Fe(H2 B(pz)2 )2 (bipy)] thin films is demonstrated. The magnetic oxide substrate locks the [FeH2 B(pz)2 2 (bipy)] largely in a low spin state. With an X-ray fluence, excitation to a high spin state occurs, while relaxation back to low spin state is aided by alternating the substrate magnetization.